Implementasi Game Edukasi Berbasis Teknologi Educandy Guna Meningkatkan Hasilbelajar Siswa Kelas V SDN Pakis V Surabaya - Putri, Nadya Eka; Desiningrum, Noviana; Yuliana, Leni (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the implementation of the technology-based educational game Educandy in improving the learning outcomes of fifth-grade students at SDN Pakis V Surabaya, especially in the subject of Natural and Social Sciences (IPAS). The background of this study is based on the low learning outcomes of students caused by conventional learning methods that are less interesting. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, documentation, and evaluation of pretests and posttests. The data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the use of Educandy can increase student motivation, involvement, and understanding of the subject matter. Observation data shows an increase in student enthusiasm for learning, while the evaluation results show an increase in the average score from 78 to 93 after the implementation of the learning media. In addition, student responses to the use of Educandy are very positive, where the majority feel more enthusiastic, confident, and understand the material better. Thus, Educandy is proven to be effective as an interactive learning media that can improve learning outcomes and create a pleasant learning atmosphere in elementary schools.